2014
DOI: 10.1371/journal.pone.0091161
|View full text |Cite
|
Sign up to set email alerts
|

Towards Improved Management of Tropical Invertebrate Fisheries: Including Time Series and Gender

Abstract: Invertebrate harvesting is an important livelihood in tropical settings providing income and food for numerous populations throughout the world. However, the lack of research, policy and management directed towards this livelihood hinders the analysis of time trends to evaluate invertebrate resources status. Another missing aspect is the consideration of gender analysis, i.e., the different roles and interests of men and women engaged in this activity. Based on interviews, catch assessments and inventories thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 30 publications
4
57
0
Order By: Relevance
“…It has been previously shown that the invertebrate population declines can take place in short periods of time in Zanzibar. For example, Fröcklin et al (2014) identified significant declines due to uncontrolled harvesting in a period of five years. In addition, there is a paucity of knowledge about species, links to their environment, and proper levels of up-take.…”
Section: Future Challengesmentioning
confidence: 99%
“…It has been previously shown that the invertebrate population declines can take place in short periods of time in Zanzibar. For example, Fröcklin et al (2014) identified significant declines due to uncontrolled harvesting in a period of five years. In addition, there is a paucity of knowledge about species, links to their environment, and proper levels of up-take.…”
Section: Future Challengesmentioning
confidence: 99%
“…Many women are engaged in seaweed mariculture and in gleaning of e.g. invertebrates (Håkansson et al 2012 ;Fröcklin et al 2014 ).…”
Section: The Stagementioning
confidence: 99%
“…Self-organization has also left women without representation in the Village Fishermen's Committees (Gustavsson et al 2014 ) which is conspicuous as a substantial number of women are engaged as collectors and some even fi shing with small nets (Fröcklin et al 2014 ). This exclusion is in line with paternalistic forms of authority that characterize communities (see below).…”
Section: The Play: Act IImentioning
confidence: 99%
“…While there is increased recognition of women’s contribution in the fisheries sector [8, 10], gender inequity persists in various facets of fisheries [8, 11] and is often overlooked in planning of fisheries management and development [9, 12]. In particular, there are few data from developing countries of comparative economic gains for men and women in fisheries [12].…”
Section: Introductionmentioning
confidence: 99%